EVOLUTION OF THE PHENOMENON OF CITIZENSHIP IN THE CONTEXT OF HISTORICAL DEVELOPMENT OF THE WESTERN EUROPE - L. Y. Maximova (Vestnik MGIMO-Universiteta)
This article analyzes the history of the development of the phenomenon of citizenship in Western Europe, from Antiquity to the Modernity. The analysis uses the binary opposition method, which is the basis for including individuals in or out of citizenship. The citizenship of Ancient Greece was of an elitist nature, sharply distinguishing citizens from the rest of the population. The basis for inclusion / exclusion was the binary oppositions “civilized – barbarians”, “free – dependent “, “possessing land ownership – not possessing such”, “adults – minors”, as a result only a small part of the population had the rights of citizens. In the Athenian democracy, for the first time in history, the basic essential characteristics of the concept of “citizen” was laid: equality, participation and liberty. The citizenship of Ancient Rome, which received the status of a limited circle of people, during the conquest of new territories included ever wider sections of population. As a result, Roman citizenship was unified, that led to the formation of the legal status of “subject of the Roman Empire,” for which no longer required property and which did not involve political participation. In the Middle Ages and Early Modern Period, for which characteristic subjection and vassalage was a type of relationship between the supreme power and the population, the phenomenon of citizenship existed only in cities. After the revolutions of the Mid Modern Period  the achievement of which was the liberation of all categories of the population and the proclamation of equality, the ideas of citizenship began to be embodied within national states. If, at the initial stage, all women and men who did not possess sufficient property were still excluded from political participation, by the end of the Mid Modern Period  all men had received a full range of civil rights. During the Modern Period women were granted the right to political participation, therefore, all adult indigenous peoples finally enter into citizenship within national states. Therefore, the list of oppositions began to include only the following: “native inhabitants of the country – foreigners” and “adults – minors”. At the same time, social rights were given special development, which enabled citizens did not worry about their survival and security. Currently, researchers note the following problems in the development of the phenomenon of citizenship: the actual remaining inequality with the declared equality of all citizens, “citizenship without participation,” when a citizen is a passive consumer of social services provided by the state. The processes of globalization led to mass migration, and it became obvious that the citizenship of the West European country is a huge privilege. The arriving population is again structured within the framework of binary oppositions: “resident - stranger”, “an European - a non-European”, “white - black (black, yellow-skinned)”, “educated - uneducated”, “ChristianMuslim” and so on. The question of inclusion / exclusion in the citizenship of Western European countries today is not fundamentally resolved. The analysis of the phenomenon of citizenship made it possible to draw a conclusion about two cycles of the development of the phenomenon of citizenship. The first cycle - Antiquity, the second cycle - the Medieval Ages and the New Time. For each of them there are some characteristic vectors of development: liberation from dependence (slavish, feudal); Inclusion of ever wider layers of the population in citizenship (the evolution of the phenomenon from elitist to mass); reduction and complete rejection of property requirements for inclusion in citizenship; reduction of active participation of citizens in government; alienation of a citizen from the state, formalization of relations between a citizen and the state. It is possible that the Modern period is the beginning of the third cycle, which will continue its development in accordance with the aforementioned vectors.